Peran Kepala Sekolah dalam Meningkatkan Karakter Islami Siswa melalui Pemberdayaan Orang Tua di SMP Muhammadiyah 2 Purbalingga - Riswanto, Riswanto; Muh. Hanif (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to explore the role of the principal in shaping students' Islamic character through parental empowerment at SMP Muhammadiyah 2 Purbalingga. The research method used is a qualitative case study with a descriptive approach, involving in-depth interviews, participatory observation, and document analysis. The results of the study indicate that the principal has successfully initiated programs such as Majelis Ta'lim, Islamic parenting, and congregational prayer policies as a form of collaboration with parents. Active parental involvement in these programs has been shown to improve students' discipline, obedience to worship, and Islamic character. The conclusion of this study confirms that synergy between schools and families, driven by the leadership of the principal, is a key factor in the success of Islamic character education. This study also recommends the development of a parent empowerment model based on Islamic values ​​that can be adopted more widely by similar schools.  Keywords: Principal, Islamic Character, School-Family Collaboration, Parent Empowerment, Islamic Education